Multiplicity dependence of inclusive J/ψ production at midrapidity in pp collisions at s=13 TeV - Acharya, S.; Adamovã, D.; Adler, A.; Adolfsson, J.; Aggarwal, M.M.; Aglieri Rinella, G.A.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; Akbar, Z.; et al. (Elsevier, 2020)
Measurements of the inclusive J/ψ yield as a function of charged-particle pseudorapidity density dNch/dη in pp collisions at √s = 13 TeV with ALICE at the LHC are reported. The J/ψ meson yield is measured at midrapidity (|y| < 0.9) in the dielectron channel, for events selected based on the charged-particle multiplicity at midrapidity (|η| < 1) and at forward rapidity (−3.7 < η < −1.7 and 2.8 < η < 5.1); both observables are normalized to their corresponding averages in minimum bias events. The increase of the normalized J/ψ yield with normalized dNch/dη is significantly stronger than linear and dependent on the transverse momentum. The data are compared to theoretical predictions, which describe the observed trends well, albeit not always quantitatively
Keywords: Multiplicity dependence; https://purl.org/pe-repo/ocde/ford#1.03.04